Heart of the jaguar : the extraordinary conservation effort to save the Americas' legendary cat - Campbell, James, III, 1961- (W.W. Norton & Company, 2025)
"Once indigenous to North America, the jaguar is one of the wildest creatures left on the planet, a resilient and efficient predator, with a natural habitat that extends throughout Mexico and Central and South America. But today, one million years after it appeared in the New World, the jaguar is struggling to survive. It has disappeared entirely from Uruguay and El Salvador, and is critically endangered across much of its range. Heart of the Jaguar tells the story of the extraordinary undertaking to save the jaguar, as well as the impassioned conservationist who dedicated his life to the species. James Campbell tracks the legacy of Alan Rabinowitz, a complex personality and a formidable scientist whom Time magazine called "the Indiana Jones of wildlife protection." Rabinowitz first studied jaguars in the jungles of Belize and the Brazilian Pantanal in the 1980s, and later led the charge for the Jaguar Corridor Initiative, making it his dying mission to protect the big cat's historic habitat. Campbell journeys across two continents in search of the species' past, present, and future, taking readers from the Bering Land Bridge to pre-Columbian jungle temples and modern-day jaguar preserves. Despite the thriving trade in jaguar parts and the ravages of industrial agriculture and climate change, Campbell finds sources of hope: wildlife biologists, Indigenous organizers, ranchers, and park administrators who carry on Rabinowitz's legacy. Compelling and clear-eyed, Heart of the Jaguar celebrates these protectors, who continue to make enormous personal sacrifices to ensure that jaguars, the most charismatic of all the big cats, always have a home on this planet." --